Dairy expansion: a case study of spring-calving pasture-based dairy production systems in Ireland. (3rd July 2020) - Ramsbottom, G.; Horan, B.; Pierce, K. M.; Roche, J. R.
Abstract: Since 1 April 2015, European dairy milk quotas have been removed resulting in the intensification of dairy production within EU countries. The aim of this study was to evaluate the physical and economic impacts of the initial intensification undertaken within Irish grazing dairy systems. Physical and financial data for 868 seasonal calving dairy farmers with records for each of the years 2013–2017 inclusive were used in this analysis. All analyses were undertaken using a mixed-model framework in PROC MIXED. The overall level of fat plus protein productivity of studied farms increased by 51% during the 5-year period through a combination of increased production per cow, increased operational scale and system intensification. Overall farm net profit was highly variable between years and was greatest in 2017 (€133 836) and least in 2016 (€65 176). When farms were characterized into milk production expansion quartiles, farms in Q1, Q2, Q3 and Q4 increased output by +7, +25, +44 and +86%, respectively. Whereas total farm profit (€/farm) declined for Q1 farms between 2013/2014 and 2016/2017 (€−5257; −7%), the greater expansion undertaken in Q2, Q3 and Q4 resulted in increases of €3046 (+4%), €20 810 (+25%) and €51 604 (+62%), respectively. In all strategies studied, farm profit increased due to a combination of increased revenues, increased pasture utilization and a dilution of per unit production costs. Further investigation of the longer term impacts of expansion is merited, not just in terms of economic indicators, but also in terms of environmental and socio-cultural change.